Analysis of Vehicle Arrivals at a Selected Intersection in the City of Zagreb - Pašagić, Husein; Kovač-Striko, Elizabeta; Perković, Gordana (Promet - Traffic&Transportation, 2012)
The paper analyses the statistics of vehicle anival at a selectedintersection in the city of Zagreb. The intersection has allthe elements of movement: going straight, left turns and rightturns. The statistic analysis in this work is based on the measurementsearned out by means of a device for gathering informationon traffic, HI-STAR Model NC-90A.We have shown that four days (Monday - Thursday) havethe same statistical regularity. Two inte1vals have been isolatedin which normal distribution can be accepted: one from 6 a. m.1012 noon and another from 1 p.m. to 4 a. m. The period from6 a.m. to 12 noon has Gauss distribution with the expectedpeaktrafficdensityalft = 9.9o’clock (i.e. atsixminutestoteno’clock) and standard deviation a = 3.1. The periods from1 p.m. to 4 a. m. have Gauss distribution with the expected peaktraffic density at fA. = 15.6 o’clock (i.e. at twenty-four minutes tosix p.m.) and standard deviation a = 4.2. The results can beused for traffic regulation at that intersection i.e. for the trafficsignal control of the intersection.